Coregulation: A Multilevel Approach via Biology and Behavior - Marc H. Bornstein; Gianluca Esposito (MDPI AG, 2023)
In this article, we explore the concept of coregulation, which encompasses the mutual adaptation between partners in response to one another's biology and behavior. Coregulation operates at both biological (hormonal and nervous system) and behavioral (affective and cognitive) levels and plays a crucial role in the development of self-regulation. Coregulation extends beyond the actions of individuals in a dyad and involves interactive contributions of both partners. We use as an example parent-child coregulation, which is pervasive and expected, as it emerges from shared genetic relatedness, cohabitation, continuous interaction, and the influence of common factors like culture, which facilitate interpersonal coregulation. We also highlight the emerging field of neural attunement, which investigates the coordination of brain-based neural activities between individuals, particularly in social interactions. Understanding the mechanisms and significance of neural attunement adds a new dimension to our understanding of coregulation and its implications for parent-child relationships and child development.